THE EFFECT OF ULIN (Eusideroxylon zwageri) STEM BARK EXTRACT ON THE GROWTH OF Candida albicans ON ACRYLIC RESIN DENTURE PLATES - Annisa Fitri Yuniar; I Wayan Arya Krishnawan Firdaus; Rahmad Arifin (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Candida albicans is the main microorganism that causes denture stomatitis, thus denture soaking in cleansing solution is needed to protect them from Candida albicans contamination. The 0.2% Chlorhexidine gluconate is one of denture cleansers that induce side effects at prolonged use. An alternative ingredient that can be used as a denture cleanser is ulin stem bark extract. Objective: To determine the effect of ulin stem bark extract at 20%, 40%, 60%, 80%, 100% concentration on the growth of Candida albicans on acrylic resin denture plates. Method: True Experimental with post-test only with control group design was employed under 7 treatment groups consisting ulin stem bark extract at 20%, 40%, 60%, 80%, 100% concentration, 0.2% Chlorhexidine gluconate, and aquadest in a total of 28 samples. Acrylic resin samples that had been exposed to Candida albicans weresoaked in respective treatment for 15 minutes. Results: The average of Candida albicans colonies on acrylic resin denture plates after soaking in ulin bark extract at 20%, 40%, 60%, 80%, 100% concentration, 0.2% Chlorhexidine gluconate, and aquadest were 29.5 CFU/ml, 13.0 CFU/ml, 0 CFU/ml, 0 CFU/ml, 0 CFU/ml, 0 CFU/ml, and 155 CFU/ml. Based on Mann Whitney test, there was no significant difference when ulin stem bark extract at 60% concentration was compared to 0.2% Chlorhexidine gluoconate. Conclusion: Ulin stem bark extract at 20%, 40%, 60%, 80%, and 100% concentration have been proven to reduce Candida albicans colonies on acrylic resin denture plates, and the 60% concentration is equivalent to 0.2% Chlorhexidine gluconate.Keywords: Candida albicans,Eusideroxylon zwageri, Heat cured acrylic resin. Ulin stem bark extract.